Information And Communication Technologies As A Means Of Developing Economic Competence Of Students - Salimov Еsanjon Xusеn o‘g‘li (Genius Journals, 2024)
In this work, the didactic possibilities of information and communication technologies, which serve to form the economic competence of students of technical higher education institutions in the conditions of the digital economy, are discussed.
Keywords: Economic entrepreneurship; digital economy; education